Posisi Penempatan dan Jenis Media Tumbuh Budidaya Bloodworm (Larva chironomus) Pada Ekosistem Rawa - Infa Minggawati (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2013)
Larvae Chironomus sp also known as blood worms with a high protein content which is a natural food mainly for fish seed. Chironomus larvae can live in the open water on the muddy grounds or fine sand rich in organic matter. This study was conducted to determine the position and placement of the right type of growing medium for the cultivation of bloodworm on swamp waters. Results of this study addressed that position kakaban good placement is horizontal in the middle with a water depth of 100 cm with an abundance of bloodworm 400-444 ind/m2. Both types of growing medium is an abundance of coconut fiber with bloodworm i 622-967 ind/m2. ANOVA analysis of the results showed that the position of the waters kakaban placement and type of growth media on the growth of different bloodworm is very real.